NEGARA HUKUM YANG DEMOKRATIS - -, Sunarno (Wacana Hukum, 2011)
Abstract : Law must go on democrazy. Law without democrazy will be repress law. In    the opposite democrazy without law  will be anarchist. This short paper want to give explaining academy about democrazy and institutionalization in law and to contect  Indonesia country, because  in  accordance  to UUD 1945 our country is a state law where the authority in the hand of people. The analizing of my short paper use to decision of Conference The International Commision of Yurist in Bangkok 1965. Key Word: The Reprensentative Government Under The Rule of Law